Mortalidade de Chrysodeixis includens (Walker, [1858]) (Lepidoptera: Noctuidae) causada por inseticidas químicos e Bacillus thuringiensis var. aizawai produzido em bioerreator industrial - Carvalho, Roberta Vieira de (2022)
Soy, Glycine max (Linnaeus) Merril, is considered the main product of Brazilian agribusiness, and its cultivation is vital to the Brazilian economy. Soy plants suffer from several phytosanitary problems since seedling emergence until physiological maturity, highlighting the attack of pest arthropods. The soybean looper, Chrysodeixis includens (Walker, [1858]) (Lepidoptera: Noctuidae), is one of the species that has been highlighting as a key pest in the crop, consuming leaves, flowers and pods. For the control of C. includens the chemical control is the most used, although it can also be used the Bt soy technology, where the plants already contain the gene of the entomopathogenic bacterium Bacillus thuringiensis (Bt) or using biological products formulated based on Bt, which can be produced on farm or using bioreactors. In this manner, the work was conducted to evaluate the efficiency of a biological product formulated with the entomopathogenic bacterium Bacillus thuringiensis var. aizawai (Bta) produced in large scale in industrial bioreactors in the control of C. includens, and its compatibility when associated with chemical control, using synthetic insecticides. The treatments consisted in the exposure of the caterpillars to isolated products and in combination, being: Bta produced in liquid solution 1 L/ha; Spinetoram (150 mL/ha); Spinetoram (80 mL/ha) + Bta (1 L/ha); Teflubenzuron (240 mL/ha); Teflubenzuron (240 mL/ha) + Bta (1 L/ha). The concentration 1 x 109 CFU/mL of Bta was used individually or in combination with the insecticides. Mortality assessment was performed 24, 48, 72 and 96 hours after application. It was observed that Bta produced in the industrial bioreactor caused mortality, greater than 95.0%, of C. includens caterpillars that ingested the bacteria after 96 hours. The spinosyn-based insecticide, individually or in mixture with Bta caused 100.0% mortality. Teflubenzuron, on the other hand, caused more than 95.0% mortality in the first 24 hours. Therefore, the bacterium Bacillus thuringiensis var. aizawai produced in industrial bioreactor was effective to cause mortality of C. includens and showed no negative interactions when associated with the insecticides spinosyn and teflubenzuron.